An Eco-Epidemiological Study on Zoonotic Cutaneous Leishmaniasis in Central Iran - Hossein NEZAMZADEH-EZHIYEH; Hossein MIRHENDI; Reza JAFARI; Arshad VEYSI; Yavar RASSI; Mohammad Ali OSHAGHI; Mohammad Hossein ARANDIAN; Hamid ABDOLI; Samad BAHRAMI; Ali Reza ZAHRAEI RAMAZANI; Reza FADAEI; Javad RAMAZANPOOR; et al. (Tehran University of Medical Sciences, 2021)
Background: Leishmaniasis is an expanding neglected tropical disease in the world reporting from 98 countries including Iran. This study focused on eco-epidemiological determinants of the disease following a rapid and unexpected increase of leishmaniasis incidence in a strategic residential district in North-East of Isfahan County, Iran. Methods: This study was accomplished from Apr 2012 to Jan 2014 in a strategic residential zone in North-East of Isfahan County, Esfahan, Iran. Monthly activity, parity, Leishmania infection and susceptibility tests, were determined on sand flies. Some portion of inhabitants and school children were surveyed to find active or passive cases of leishmaniasis and also wild rodents were collected to determine reservoir host. Results: Totally 5223 sand flies belonging to Phlebotomus and Sergentomyia genus were collected and identified; Ph. papatasi was the dominant species and started to appear in May and disappeared in Oct. The majority of living dissected sand flies were unfed and parous. Ph. papatasi showed 4.6% Leishmania infection through direct examination and 39.54% by nested-PCR respectively. Phlebotomus papatasi was susceptible against deltametrin 0.05%. Totally 2149 people were surveyed and incidence and prevalence of zoonotic cutaneous leishmaniasis estimated as 45.39 and 314.40 per 1000 population. Rodents showed 73.91% and 80% Leishmania infection by direct examination and nested-PCR respectively. Conclusion: Cutaneous leishmaniasis due to L. major has been established in this area. Rodent control operation and personal protection are highly recommended to control the disease in this focus.